A novel method for assessing the chromatic integration of architecture in the Ksourian landscape of M'zab Valley, Algeria. Issue 5 (30th March 2018) - Gouaich, Yacine; Mebrouki, Abdelkader; Ghariri, Racha; Mebarki, Abdelkhaliq; Belabbas, Akila; Manav, Banu; Serra, Juan; Llopis, Jorge; Torres, Ana
Abstract: Ksour are original architectural models of fortified villages located in the north of Africa. They offer, through their urban and natural visual sceneries, specific visible features that we name them Ksourian Landscapes . The present research, accordingly, addresses an investigation; relying on a new methodic perspective, of the chromatic character of the Ksourian landscape of M'zab valley in Algeria which is listed as an UNESCO World Heritage Site. Using the Natural Color System (NCS), a natural palette (NP) has been conducted; encapsulating 12 representative colors from the natural landscape of the site in congruence with a second palette (human settlements palette), which includes around 16 colors from the urban landscape of the Mozabite Ksour . The primary purpose of this research article aims at identifying perceptual similarities between the two palettes after comparison; which relies upon the NCS nominal identities (blackness [ s ], whiteness [ w ], chromaticness [ c ], yellowness [ y ], and redness [ r ]); and the NCS relation identities (hue [φ], saturation [ m ], delta [δ], and beta [β]). Graphical representations of these comparisons are demonstrated in the NCS triangle and the NCS 3D color space. We have demonstrated through our experimental outcomes the strong chromatic integration of the urban settlements in their natural landscape, the original chromatic character as being a constituent of the heritage values of the Mozabite Ksourian landscape, as well as its possible use in the urban restoration processes.